Respostas
respondido por:
8
16 + [10-(18:3+2)+5]
16+[10- (8) +5]
16 + [10-13]
16 +[3] =
16 +3 = 19
25 -[12 - (3x2 +1)]
25-[12- ( 7)]
25-5= 20
[40+2x(7-5)]x2 -20
[40 +2 x (2)] x2 -20
[40 +2 x (4)] -20
[40 +2 x (16)]
[40 +32 ] =
72
Foi assim que eu entendi
16+[10- (8) +5]
16 + [10-13]
16 +[3] =
16 +3 = 19
25 -[12 - (3x2 +1)]
25-[12- ( 7)]
25-5= 20
[40+2x(7-5)]x2 -20
[40 +2 x (2)] x2 -20
[40 +2 x (4)] -20
[40 +2 x (16)]
[40 +32 ] =
72
Foi assim que eu entendi
lufreitas76:
Eu so esqueci de coloca um numero na primeira16+[10-(18:3+2)+5]
16+[10- (8) +5]
16 + [10-13]
16 +[3] =
16 +3 = 19
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás